Stock Liquidity and Share Returns: Evidence from Mining Companies Listed on Johannesburg Stock Exchange - Moyana, Simbarashe; Magwedere, Margaret Rutendo; Marozva, Godfrey (International Journal of Energy Economics and Policy, 2026)
The study was aimed at examining the relationship between stock liquidity and share returns within mining sector companies listed on the Johannesburg Stock Exchange (JSE). The study was pursued after realising a failure by the mining sector to reach its full potential, regardless of the presence of vast deposits of mineral resources. A need therefore is required to ensure that the various stakeholders gain trust within the sector for the purposes of enhancing investment. The study was undertaken using a quantitative methodology and panel data analysis technique through generalised methods of moments (GMM). A sample of 15 listed companies on the JSE was selected based on data availability, with 14-year data spanning from 2011 to 2024. The independent variable was stock liquidity, while stock returns represented the dependent variable and various control variables. The results from the study showed that there is a positive relationship between stock returns (SR) and price to earnings ratio, return on market, Amihud illiquidity measure (ILLIIQ), while SR had a negative relationship with volume of trade and size. The results from the study pose a positive effect towards existing and potential investors in their assessment when making investment decisions.